THE PERFORMANCE OF APPLE CHIPS SUPPLY CHAIN MANAGEMENT AT SMALL INDUSTRY IN BATU CITY - Dwi Retnonigsih (Socio-Economics/Agribusiness Department, 2018)
Batu City is one of well known cities in East Java Province which is as center of tourism destination and also as center of apple production. There is growing small scale industry related to apple processed products, such as apple chips. In an effort to support the supply of raw materials and production planning, it is necessary to know the achievement of supply chain performance in a small industry of apples chips in Batu City. The method used is qualitative analysis to know the system of raw material inventory control and production planning system applied and analyze the performance of supply chain management, supply chain mapping with SCOR (Supply Chain Operations Reference) method, measurement of supply chain performance by using measured performance attribute that is Supply Chain Reliability, Supply Chain Responsiveness and Supply Chain Agility with performance metrics of Perfect Order Fulfillment (POF), Order Fulfillment Cycle Time (OFCT), Upside Supply Chain Flexibility, Upside Supply Chain Adaptability and Downside Supply Chain Adaptability. The results of this study indicate that the system of raw material inventory control and production planning system have been applied. Supply chain mapping, performance measurement of supply chain management need to be developed more to improve supply chain management performance in the small industry apple chips in Batu City.